1997
DOI: 10.1258/0956462971919688
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 infection in AIDS patients

Abstract: Bone marrow of 61 HIV-1-infected patients and 23 control patients was examined to determine the incidence of B19 infection and its clinical impact in HIV-1-infected persons. Of the 61 HIV-infected patients studied, ages ranged from 22-47 years with a mean of 33.2 years. There was a man:woman ratio of 3.8:1. With regard to staging of HIV disease at the time of bone marrow sampling, 52 patients were CDC group 4, 5 patients were CDC group 3, and 4 patients were CDC group 2. Control patients, were not known to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…B19 DNA has been shown to persist in various sites including bone marrow [135], synovium [136], testis [137], skin [138] and blood [139]. However, the mechanism of persistence is unclear.…”
Section: B19 Persistencementioning
confidence: 99%
“…B19 DNA has been shown to persist in various sites including bone marrow [135], synovium [136], testis [137], skin [138] and blood [139]. However, the mechanism of persistence is unclear.…”
Section: B19 Persistencementioning
confidence: 99%
“…Cell types infected by B19 virus include erythroblasts, megakaryoblasts, granulocytes, macrophages, follicular dendritic cells, T and B lymphocytes, hepatocytes, and endothelial cells 4049 79 80 B19 virus DNA has been shown to persist in various sites of the human body, including bone marrow,81 synovium,80 82 83testis,84 and skin,85 but the mechanism which facilitates this persistence is unclear. In one study B19 viraemia was shown to occur in seven of 53 subjects, 3–5 years after acute B19 infection 86…”
Section: Pathogenesis Of Disease Associated With B19 Infectionmentioning
confidence: 99%
“…It has been reported that, in immunodeficient patients, failure to clear B19 virus may produce persistent infections, which lead to chronic anemia. [3][4][5][6]8 Thus, the eradication of B19 in this HIV-infected patient may be attributed to an increase in cellular immunity brought about by HAART (CD4 cell counts: November, 1997, 195 cells/µl; February, 1999, 422 cells/µl). Although B19 is generally spread by a respiratory route of transmission, blood products that were not checked for B19 contamination could be the source of transmission.…”
Section: Discussionmentioning
confidence: 90%